Implementasi Pembelajaran Guru Dalam Meningkatkan Perkembangan Bahasa Anak Di RA Al-Jihadiyah Bekasi - Anastasya Puspita Hafidz; Hafidz, Aulia Putri Pratiwi; Mutiara (Fakultas Tarbiyah IIQ Jakarta, 2022)
Research or observation is done to determine the indication of talk delay and handle children with a 4-6-year-old talk. This research is based on or based on our sense of our currency (author of children) of the child who exhausts the talk of the child and language of the child, especially at the age of 4-6 years. Talk and language disorders are one of the causes of growing children's growth that are often encountered. The methods undertaken by us are by interviewing the informant (teacher) directly at TK Ra al-Jihadiyah. The resourcesakenakers taken in this observation amounted to 2 informants with details 1 as Ra's headmaster, and the 2th is the teacher (educator) in RA itself. The results of our observations, there are several obstacles and how handling we have obtained: Language of disorders, difficulty understanding something, difficulties following clues or directives, a little communication, do not want to learn, parents are too demanding, and articulation or pronunciation. As for how to handle it, more attention from the parents and the teacher, intense communication in its environment is, and the language training by Mother to her son and teachers to the students.